2005
DOI: 10.1590/s1413-86702005000500030
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of B Non-Hodgkin's Lymphoma in children: the experience of multicentre studies and Brazilian National Cancer Institute's experience

Abstract: case each). The presence of bone involvement was observed in 23.7% of the patients and 3.9% presented CNS involvement. Time to diagnosis ranged from 1 to 210 days (mean = 47.1 days). The mean LDH was 2,014 U/mL (range 91U to 36,599U). 51 patients had immunephenotyping, 23 confirmed B (Burkitt´s) NHL, 13 T NHL patients, 2 T angiocentric NHL patients (one nasal e one testicular), 2 mediastinal diffuse large cell NHL patients (B), 4 abdominal diffuse large cell NHL patients (B), 7 large cell anaplastic lymphoma p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…Surprisingly, baseline LDH failed to show any correlation with survival figures, as opposed to what other centers have observed, probably because of the fact that ours was a retrospective analysis and we could not gather this information in a significant minority of our patients, 1 although it is not a universal finding and there are examples in the international literature which do not favor high LDH as an adverse prognostic factor 2,7,17 . Our figures also do not suggest any relationship of baseline uric acid with TLS and its associated mortality but this may have been because of the missing values for some of our patients.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Surprisingly, baseline LDH failed to show any correlation with survival figures, as opposed to what other centers have observed, probably because of the fact that ours was a retrospective analysis and we could not gather this information in a significant minority of our patients, 1 although it is not a universal finding and there are examples in the international literature which do not favor high LDH as an adverse prognostic factor 2,7,17 . Our figures also do not suggest any relationship of baseline uric acid with TLS and its associated mortality but this may have been because of the missing values for some of our patients.…”
Section: Discussioncontrasting
confidence: 93%
“…The patients in our study who died also showed an average time interval of only 35 days between diagnosis and death, with 21 deaths (46 percent) occurring within the first 30 days of starting treatment. This association of advanced disease with early death is well documented in the literature, where not just lymphomas but various other cancers have been shown to behave in a similar manner in this context 2,15 . The factors related to advanced presentation and hence poor outcomes in our study were the lack of health education among the general population, living far away from a health facility, delays in recognition of early signs of disease and poor health infrastructure.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation